An Analysis of Semarang City Residents' Interest in Using Trans Jateng - Egies Mauliddya (Shipping and Transport Management Journal, 2025)
This study aims to analyze the interest of residents of Semarang City in using the Trans Jateng service and to identify the factors that influence this interest. The background of this study is the low proportion of residents switching to public transportation despite the availability of the Trans Jateng service. This research adopts a quantitative approach, utilizing a survey method to collect data, which is then processed using SPSS software. The results of the study indicate that factors such as service quality (including service, comfort, and safety), fare perception, and stop access significantly influence the interest of residents in using Trans Jateng. These findings are valuable for understanding the factors that drive the adoption of public transportation in urban areas. The novelty of this study lies in its specific focus on Semarang City and the integration of resident interest variables with the relatively new Trans Jateng service in the region. The study’s implications offer practical recommendations for public transport operators to improve fare policies, enhance promotional strategies, and optimize modal integration to encourage greater use of public transportation.